+0  
 
0
399
1
avatar

If g(x) = -2x^2-3. Find g(0).

 Jun 24, 2017
edited by Guest  Jun 24, 2017

Best Answer 

 #1
avatar+7352 
+2

g(x)   =  -2x2 - 3                 To find  g(0)  , replace every instance of  " x "  with  " 0 "  .

 

g(0)  =  -2(0)2 - 3                (0)2  =  0

 

g(0)  =  -2(0) - 3                 -2(0)  =  0

 

g(0)  =  0 - 3

 

g(0)  =  -3

 Jun 24, 2017
 #1
avatar+7352 
+2
Best Answer

g(x)   =  -2x2 - 3                 To find  g(0)  , replace every instance of  " x "  with  " 0 "  .

 

g(0)  =  -2(0)2 - 3                (0)2  =  0

 

g(0)  =  -2(0) - 3                 -2(0)  =  0

 

g(0)  =  0 - 3

 

g(0)  =  -3

hectictar Jun 24, 2017

10 Online Users

avatar